Herbicide Adoption Pattern of Cotton Farmers in Vidarbha (Indian Journal of Extension Education, 2017)
A systematic extensive survey of 240 cotton growers on herbicide adoption was conducted in Vidarbha region of Maharashtra during 2013-2014. The study revealed that 48.17 percent cotton growers have applied herbicides during 2013-14 for control of weeds in cotton crop. Knowledge about recommended per ha doses of herbicide is not known to 62.50 per cent farmers. Overall 52.90 percent farmers have medium level of knowledge about selected 15 herbicide application practices for cotton crop. Out of the total 118 (48.17%) herbicide adopters in cotton 25 (21.18 %) farmers applied only single spray of post-emergence/selective herbicide, followed by 30.52 per cent herbicide adopter farmers applied two applications of herbicides, first applied post-emergence/selective herbicides and in second application they have used glyphosate as non-selective herbicide and remaining 48.30 per cent farmers had applied single spray of ‘glyphosate’ at 50 DAS in cotton. Majority herbicides users applied the recommended dose in cotton crop. Out of the total 118 (49.17 %) herbicide adopters majority 101(85.60 %) farmers have used knapsack sprayer in cotton. Cent percent (100%) farmers has not done the calibration of sprayer pump. Out of the total 118 (49.17 %) adopters 93 (78.81%) farmers have used non selective herbicides in cotton and out of them majority 88.17 per cent farmers used the hood for protective application. Out of total 118 (49.17%) adopters only 27.97 per cent farmers used recommended 500 liters of water /ha in cotton crop. Overall cotton farmer’s choice was Pyrithiobac sodium (Hitweed) and glyphosate. Over half (62.50%) of the farmers expressed that they are not getting the proper information about herbicide applications from extension functionaries of the Government, hence the State Department of Agriculture should organize regular trainings/ workshops, demonstrations, preparation and distribution of printed material about use of herbicides before sowing season with the expertise of SAU scientists so that cotton cultivators in Vidarbha will get technical knowledge for effective use of herbicides.